2022
DOI: 10.54393/pbmj.v5i3.328
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness of Sickle Cell Anemia: Cross Sectional Study among the General Population in Saudi Arabia

Abstract: Sickle cell disease (SCD) is a hereditary blood disorder. The red blood cells are sickle in shape by polymerization of the Hemoglobin molecule caused by a β-globin gene defect that leads to Substitution of valine for glutamic acid in position 6 of the β-globin. It's an autosomal recessive inherited hematological disease. In Saudi Arabia, the prevalence of the sickle cell gene in the adult population is (4.2%) for sickle-cell trait and (0.26%) for SCD, with the highest prevalence was found in the eastern region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We collected the information using a Google form questionnaire. This structured questionnaire used in this study was taken from previous conducted study (Khalifa et al, 2022).…”
Section: Methods For Data Collection and Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected the information using a Google form questionnaire. This structured questionnaire used in this study was taken from previous conducted study (Khalifa et al, 2022).…”
Section: Methods For Data Collection and Instrumentmentioning
confidence: 99%
“…Only 53 people (13.3 percent) were aware of the effect illness had on children when both of their parents suffered from it. There was a 97.5 percent consensus among 390 participants about the significance of premarital counseling (Khalifa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The data was gathered through the utilization of a questionnaire administered via a Google form. The structured questionnaire employed in this study was derived from a previously completed study (Khalifa et al, 2022).…”
Section: Methods For Data Collection and Instrumentmentioning
confidence: 99%
“…A few 53 individuals, constituting 13.3 percent of the sample, demonstrated awareness regarding the impact of disease on children in cases where both parents were afflicted. According to Khalifa et al (2022), a study involving 390 participants revealed a consensus rate of 97.5% on the importance of premarital counseling.…”
Section: Suggested Citationmentioning
confidence: 99%